Upaya Mahasantri Dari Latar Belakang Non Pesantren Dalam Menghafal Al-Qur'an Di Ma'had Al- Jami'ah UIN Fatmawati Sukarno Bengkulu - Apriyanti, Ginta; Khoiri, Qolbi; Chandra, Pasmah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Based on initial observations, this study explores the obstacles and challenges faced by non-pesantren students in the process of memorizing the Qur'an at Ma'had al-Jamiah UIN Fatmawati Sukarno Bengkulu. Compared to pesantren students, non-pesantren students face unique challenges due to their lack of previous experience in studying the Qur'an, different learning environments, and limited knowledge of the Qur'an. Nevertheless, non-pesantren students have great potential to succeed in memorizing the Qur'an and contribute to the development of education at Ma'had al-Jamiah. This study discusses the efforts of students from non-pesantren backgrounds in the process of memorizing the Qur'an at Ma'had Al-Jami'ah UIN Fatmawati Sukarno Bengkulu. This type of research is qualitative field research. The subjects of this study were students from non-pesantren backgrounds consisting of 20 students. Data collection was carried out by researchers through observation, interviews and documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The primary data sources of this study were 20 students from non-Islamic boarding school backgrounds and Quran memorization instructors at the Al-Jami'ah Islamic Boarding School, UIN Fatmawati Sukarno Bengkulu. Based on the results of this study, it shows that the efforts of students in memorizing the Qur'an involve consistency in intentions and goals, setting time targets, time effectiveness, consistency in memorization, various memorization methods, and setting daily memorization targets. Factors that influence non-Islamic boarding school students in memorizing the Qur'an include family support, optimization of memorization targets, college assignments, memorizing long verses, and laziness. In addition, social support and the surrounding environment also play an important role, including the environment of friendship, guidance from ustadz/ustadzah, and guidance from musrifah/musrifah at the Al-Jami'ah Islamic Boarding School.